Analisis Interaksi Antar Pemain dan Alasan Trash-Talking dalam Penggunaan Fitur Teks dan Voice Chat pada Game Online Valorant - Aulia, M. Irsyadil; lestari, yayuk; Anindya, Annisa (AL MUNIR : Jurnal Komunikasi dan Penyiaran Islam, 2024)
This study analyzes player interactions and the reasons for trash-talking in the use of text and voice chat features in the online game Valorant. The background of this research is based on the lack of studies on the differences in the use and impact of text and voice chat, as well as their influence on game dynamics and player behavior. The theory utilized in this research is Computer Mediated Communication (CMC), which highlights how communication through computer media can shape behavior and group dynamics. The research method employed is qualitative analysis with an observational approach and in-depth interviews with active players. The findings indicate that player interactions through text chat are more frequently used for strategic communication, while voice chat is more often employed for quick and intense communication. Trash-talking often occurs as a form of dominance expression, psychological strategy, and emotional reaction to in-game situations. These findings underscore the importance of managing communication in games to create a healthy and positive gaming environment.